Resolution of Elevated Urine Glycosaminoglycans and Clinical Features of Mucopolysaccharidosis After Successful Treatment of Neuroblastoma. Issue 6 (August 2016) - Hilgers, Megan V.; Whitley, Chester B.; Moertel, Christopher L.
Abstract : We report a patient with stage 3 ganglioneuroblastoma who initially presented with clinical and laboratory features consistent with mucopolysaccharidosis including coarse facial features, developmental delay, and an elevated quantitative urine glycosaminoglycan (GAG) level. All mucopolysaccharidosis features resolved following successful treatment of neuroblastoma. High GAG levels have been documented in the pediatric oncology literature, yet not as a potential marker of malignancy or other target for clinical utility. This patient prompts further investigation into the relationship between neuroblastoma and elevated GAG levels.